2020
DOI: 10.3390/medicina56070323
|View full text |Cite
|
Sign up to set email alerts
|

Dupuytren’s Contracture: Incidence of Injury-Induced Cases and Specific Clinical Expression

Abstract: Background and objectives: Dupuytren’s contracture is a chronic fibroproliferative hand disorder with a varying pattern of genetic predisposition across different regions and populations. Traumatic events have been found to have influence on the development of this illness and are likely to trigger different clinical forms of this disease. The aim of this study was to evaluate the phenomenon of development of Dupuytren’s contracture (DC) following an acute injury to the hand, and to observe the incidence and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The response to non invasive therapy was remarkable without any recurrence at short term. The dupuytren's contracture is a fibroproliferative disease, commonly seen in the elderly people and is one of its risk factors (6). The treatment has options with needle injections, and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The response to non invasive therapy was remarkable without any recurrence at short term. The dupuytren's contracture is a fibroproliferative disease, commonly seen in the elderly people and is one of its risk factors (6). The treatment has options with needle injections, and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest posted details and description of the problem was reported in 1614 by Felix Platter, yet it was Guillian Dupuytren who introduced a careful anatomic and obsessive investigation in 1831. What was extraordinary about palmar fibromatosis was that he accentuated the clinical course of the illness, the palmar fibromatosis influencing the hands frequently brings about constraints in aptitude and can fundamentally affect a person's capacity to participate in professional and a vocational exercises [15]. The condition is a significant reason for morbidity which diminishes their personal satisfaction, patients report feeling danger concerns, communicating dread that the fixed flexion of the finger will make it more defenseless to wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing this criterion, a 2020 study found approximately 20% of their Dupuytren's cases were injury induced (1). Even as the literature on this topic has progressed and diagnostic criteria have been developed, familiarity with this phenomenon seems to be isolated to orthopedic hand specialists.…”
mentioning
confidence: 99%
“…Dupuytren's disease is inherited in an autosomal dominant pattern although other associations include age (i.e., older than 50 years), male sex, genetic predisposition (i.e., Northern European origin), alcoholism, human immunodeficiency virus, vascular disease, diabetes mellitus, and epilepsy (1,2). A Dupuytren's contracture progresses through proliferative, involution, and residual phases.…”
mentioning
confidence: 99%
See 1 more Smart Citation